Verby objektivisme en relativisme: Op weg na nuwe fondamente vir historiese Jesus-studies - Ingram, Riaan (HTS teologiese studies, 2004)
Beyond objectivism and relativism: Towards new foundations for historical Jesus studiesIn light of the contemporary epistemological discussion with regard to historical Jesus-studies and historiography in general, recent scholarship proposes that historical criticism and creativity should be combined to form a contemporary relevant picture of Jesus as historical figure. Some philosophical insights produced during the last century also suggest that western civilisation has become preoccupied with the essence of things and has forgotten that people are essentially ethical beings in need of wisdom. This tendency is also revealed in the recent preoccupation with the “truth” regarding Jesus’ life. In this article these issues are elaborated upon in discussion with especially Heidegger, Bernstein and Gadamer. Eventually the insights gained by this discussion are illustrated with regard to historical Jesus studies.